Design of a Bicycle's Structural Components and a Comparison of Their Characteristics in Steel, Aluminum and Carbon - Pompáš, Lukáš; Brumerčík, František; Kučera, Ľuboš; Smetanka, Lukáš (Communications - Scientific Letters of the University of Zilina, 2023)
The design of a bicycle frame in Creo Parametric and the following simulation comparison of three frame materials - steel, aluminium and carbon, using the software from Marc Mentat, are the main subjects of this article. In this article, the authors explain how to model a bicycle frame in three dimensions and contrast it with frames made of the other two materials. The simulation's findings demonstrate how various elements, such as load, affect a steel, aluminium and carbon frame's behaviour in specific circumstances and under identical settings. Engineers may choose the best material and optimize the geometry and topology of the frame, based on the findings of the simulation, to get the best outcomes in terms of the stiffness requirements and rider comfort.
Keywords: bike frame; materials; simulation; bicycle